Penerapan Hiasan Tucking Ballen Pada Evening Gown Dan Busana Pria - Killi, Frigelia Rebeka; Russanti, Irma (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The application of embellishments in clothing aims to enhance aesthetics and increase visual appeal. One technique that can be used is tucking, a fabric manipulation method involving repeated folds that are stitched to prevent movement. This technique is often applied to both garments and household linens. In this study, tucking ballen is used as an ornament on evening gowns and men's suits, creating a more unique and elegant fabric structure. The research employs the Double Diamond Design Process, which consists of four stages: discover, define, develop, and deliver. The design theme, borderless fusion, integrates traditional cultural elements with modern aesthetics. The fabrics used include Satin Duchess, glitter tulle, and wool, incorporating the tucking ballen technique. This study resulted in a collection of men's and women's evening wear showcased at the 2nd Annual Fashion Show of the D4 Fashion Design Program at UNESA. Findings indicate that the tucking ballen technique not only enhances the aesthetic value of garments but also provides an innovative structural element. This technique holds further potential for development in haute couture designs and can be combined with other fabric manipulation techniques to create more intricate and artistic designs.